TINGKAT KECEMASAN DENGAN KUALITAS TIDUR IBU HAMIL PRIMIGRAVIDA TRIMESTER III - Wardani, Hartanti Wisnu; Agustina, Rismia; Damayanti, Emmelia Astika F. (Dunia Keperawatan: Jurnal Keperawatan dan Kesehatan, 2018)
The pregnant women experienced anxiety at the end of pregnancy especially the first pregnancy(primigravidae). The previous of the study on 10 pregnant women in primigravidae trimester IIIshowed 9 pregnant women experienced anxiety and all of the pregnant women appraised thequality of sleep was felt bad enough. The objective of the research was to know the correlationbetween the level of anxiety with the quality of sleep on the pregnant women in primigravidaetrimester III at Idaman General Hospital Banjarbaru. The method of this research was thecorrelation research with cross sectional design on 30 pregnant women in primigravidaetrimester III at Idaman General Hospital Banjarbaru. The instruments of the research werePittsburgh Sleep Quality Index and Pregnancy Related Anxiety Questionnaire-Revised 2 (PRAQR2). The data analysis used correlation Spearman test. The analysis of correlation showed thatthe levelof anxiety was significant related to the quality of sleep primigravidae trimester IIIpregnant women (p value=0.013, r=0.449). The level of anxiety influenced the quality of sleepprimigravidae trimester III pregnant women. The lower the level of anxiety is, the better the sleepquality of sleep gets.